2006
DOI: 10.1300/j115v25n04_02
|View full text |Cite
|
Sign up to set email alerts
|

Information Literacy and Library Attitudes of Occupational Therapy Students

Abstract: ABSTRACT. Information literacy, often described as a person's ability to effectively find and evaluate answers to questions using a variety of information resources, is of particular importance to health care workers. This paper presents the results of an information literacy survey presented to occupational therapy (OT) students at Thomas Jefferson University during a series of required class activities. Also described are the authors' activities with the faculty and courses at Jefferson.The survey was made a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Similar to participants in Kipnis and Frisby's study [10], 82% of students in this study expected to learn information literacy skills through trial and error, while working on their own. Students expressed the need to spend more time practicing searching and evaluating documents, using both their library and the Internet.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Similar to participants in Kipnis and Frisby's study [10], 82% of students in this study expected to learn information literacy skills through trial and error, while working on their own. Students expressed the need to spend more time practicing searching and evaluating documents, using both their library and the Internet.…”
Section: Discussionmentioning
confidence: 65%
“…Second, it offered a list of external links to resources for building health information skills that students could explore on their own. Contrary to participants in the Kipnis and Erisby study [10], students who participated in this study identified librarians, not peers, as their first line of assistance if they chose to ask for research help. Over half of all study participants (99 out of 181) mentioned contacts with librarians as a competency-building approach.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The following barriers to information needs resolution were discerned: information literacy (IL) skills, awareness of library collections, and the accessibility and availability of information services and resources. Preferences for particular information resources were influenced by these barriers, as well as by each user group's tasks and role requirements . These themes directly informed the study's research objectives and methodology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most common motivators for informationseeking were completing academic assignments, acquiring workplace skills and adhering to evidence-based practice (EBP) on placements. [6][7][8] The following barriers to information needs resolution were discerned: information literacy (IL) skills, awareness of library collections, and the accessibility and availability of information services and resources. Preferences for particular information resources were influenced by these barriers, as well as by each user group's tasks and role requirements.…”
Section: Literature Reviewmentioning
confidence: 99%